3D Boundary element meshing for multiscale bone anisotropic analysis. Issue 5 (2nd November 2018) - Prada, D. M.; Galvis, A. F.; Alcântara, A. C.; Sollero, P.
ABSTRACT: Bone health conditions are treated with prosthesis and implant fixations. Despite being there to assist the patient, the difference between the elastic properties of these artificial medical solutions and the treated bone region may lead to a new fracture. One strategy to circumvent that problem, reducing the gap between the elastic properties, is to use Functionally Graded Materials in the manufacture of such medical devices. It is therefore of vital importance to understand the mechanical properties of bone within the region of interest, once this knowledge may ease and improve the development of artificial medical solutions. The bone tissue is a hierarchical material which has different elastic behaviour depending upon the scale of interest, the particular bone and the bone region. In this work, a multi-scale BEM mesh model of bone tissue ranging from the nanoscale to the mesoscale is sought. A new nanoscale design which considers the hydroxyapatite crystals inside, and outside the fibrils is developed. Furthermore, the fibrils are modelled with reported elliptical cross sections. Additionally, a procedure to develop the BEM meshes using multimedia software is proposed, based upon the similarities between them. Finally, several mesheswere created using triangular continuous elements.